Konsep Missing Link Menstimulasi Pandangan Generasi Alpha (Asal Usul Manusia) - Pariyanto Pariyanto; Tomi Hidayat (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2020)
The purpose of writing this article is an attempt to uncover the concept of the missing link on human origins (the theory of evolution). Researchers want to stimulate the views of the Alpha generation to have another view, we know that most of the present generation still believes in the origin of living things from apes. The method used is the literature review method, the study is carried out on journals, books and other sources that are relevant and can be guaranteed its validity. Search results and studies, the authors found the concept if this theory has actually been questioned since the development of science in ancient Rome and Greece. Broadly speaking, this theory states that living things that exist in the world up to now are the result of the development of creatures that have existed before, both concerning structure and function, hereditary from generation to generation. Thus, the change which is the result of development takes place in a very long time, that is, millions of years along with the evolution of the universe. This theory is not entirely wrong, the problem is that the theory is only a theory that is not strengthened by physical evidence so that Darwin's theory is widely doubted from various circles. With the concept of Missing Link is one proof that humans do not originate from apes. This is due to the fact that no transitional creatures have been discovered from any changes that occur between species. In conclusion, the concept of the missing link becomes a reference to stimulate the generation of alpha in understanding the concept of evolution put forward by Darwin and refutes the process of the origin of man himself put forward in Darwin's theory of evolution. Key words: Missing Link, Stimulate, Theory of Human Evolution.